2018
DOI: 10.3390/su10114084
|View full text |Cite
|
Sign up to set email alerts
|

Age Factor and Pedestrian Speed on Sidewalks

Abstract: Pedestrian infrastructures feature the spaces where every user accesses all the mobility forms: in fact, every movement begins and finishes with a walking section. For this reason, it is very important to pay more attention towards what is said "last mile", that must be designed and constructed to be easily used from the major part of users, with a special attention to more disadvantage citizens. Among all pedestrian characteristics, the least considered is speed, and when it is considered, the reference is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…In turn, females tend to be more cautious about the safety and security risks associated with walking than males [53,54]. Elderly pedestrians and seniors may have more time and flexibility to walk, but due to aging, they not only lose some skills, such as less walking speed, stable balance and wayfinding capabilities, but also have more unsafe crossing behaviors [2,5]. However, findings of the impact of age on walking are not consensual.…”
Section: Influence Of Individual Variables On Utilitarian Walkingmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, females tend to be more cautious about the safety and security risks associated with walking than males [53,54]. Elderly pedestrians and seniors may have more time and flexibility to walk, but due to aging, they not only lose some skills, such as less walking speed, stable balance and wayfinding capabilities, but also have more unsafe crossing behaviors [2,5]. However, findings of the impact of age on walking are not consensual.…”
Section: Influence Of Individual Variables On Utilitarian Walkingmentioning
confidence: 99%
“…Walking reduces the negative environmental impacts caused by motorized traffic in terms of CO 2 , air pollutants, and noise [4]. For that reason, replacing short car trips with walking trips has an important role in making our cities more sustainable [5]. Walking is also an active mode of transport and the most widely available form of physical activity that helps to prevent various physiological and mental diseases associated with sedentary lifestyles, such as obesity, diabetes, and depression [6].…”
Section: Introductionmentioning
confidence: 99%
“…Everybody has his/her own desired walking speed. It is influenced by many factors such as intention outlook, age, and gender [13,28,29,32]. We have used Gaussian distribution model, which offers a normal distribution pattern similar to real-world scenarios.…”
Section: Social Force Modelmentioning
confidence: 99%
“…Guo et al (2016) [53] tested the functions of parallelogram-shaped pavement markings based on an experiment, and the results showed that the use of parallelogram-shaped 5 of 46 pavement markings helped in reducing both the frequency and severity of crashes at pedestrian crosswalks by reducing the proportion of drivers exceeding the speed limit by an average of 11.03%. Pinna et al (2018) [54] proposed that the least considered among all pedestrian characteristics is speed. Guido et al (2019) [55] investigated the correlation between real accident locations and simulated risk areas in Cosenza based on a microscopic framework and indicated that traffic conflict techniques had a positive effect on improving PT safety.…”
Section: Transportation Factormentioning
confidence: 99%